2020
DOI: 10.1007/s00423-020-02043-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of conversion in minimally invasive distal pancreatectomy: a systematic review

Abstract: Purpose The reported conversion rates for minimally invasive distal pancreatectomy (MIDP) range widely from 2 to 38%. The identification of risk factors for conversion may help surgeons during preoperative planning and patient counseling. Moreover, the impact of conversion on outcomes of MIDP is unknown. Methods A systematic review was conducted as part of the 2019 Miami International Evidence-Based Guidelines on Minimally Invasive Pancreas Resection (IG-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…These findings suggest that a low-risk cohort mainly results in lower rates of conversion, morbidity, and readmission, and to a lesser extent affects parameters such as operating time, duration of hospital stay, and spleen preservation. Previous literature supports these findings given the exclusion criteria used for the low-risk cohort in which the best-patient-in-best-centre benchmarks were established; extended or multivisceral resections, ASA grade at least III, major previous abdominal surgery, and BMI 35 kg/m² or higher have been associated with higher rates of conversion and postoperative morbidity [36][37][38][39] . Excluding such patients may have resulted in better outcomes and thus led to stricter best-patient-in-best-centre 75th percentiles compared with the ABC 75th percentiles.…”
Section: Discussionmentioning
confidence: 60%
“…These findings suggest that a low-risk cohort mainly results in lower rates of conversion, morbidity, and readmission, and to a lesser extent affects parameters such as operating time, duration of hospital stay, and spleen preservation. Previous literature supports these findings given the exclusion criteria used for the low-risk cohort in which the best-patient-in-best-centre benchmarks were established; extended or multivisceral resections, ASA grade at least III, major previous abdominal surgery, and BMI 35 kg/m² or higher have been associated with higher rates of conversion and postoperative morbidity [36][37][38][39] . Excluding such patients may have resulted in better outcomes and thus led to stricter best-patient-in-best-centre 75th percentiles compared with the ABC 75th percentiles.…”
Section: Discussionmentioning
confidence: 60%
“…The study results demonstrated that the judgment of the surgical skill and the level of the learning curve of the pancreatic surgeon cannot be left out of consideration in the conversion rate and EBL. The use of these indicators as surrogates of surgical difficulty of these parameters has been widely reported in the literature 26,27 . The preoperative patient's characteristics, particularly the body mass index, did not result as additional factors of the complexity of the surgical procedure 28 .…”
Section: Discussionmentioning
confidence: 94%
“…The use of these indicators as surrogates of surgical difficulty of these parameters has been widely reported in the literature. 26,27 The preoperative patient's characteristics, particularly the body mass index, did not result as additional factors of the complexity of the surgical procedure. 28 Notably, the postoperative outcomes were not influenced by the surgical complexity based on the mDSS, in contrast with previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Benefits of RDP such as the lower conversion rates have been described 8 10 and are mainly attributed to the technical features of the robotic system providing the surgeon with more freedom of movement and better bleeding control. Although conversion in certain circumstances is necessary for a safe progression and to ensure adequate oncological clearance, literature has demonstrated that patients requiring conversion to open surgery in MIDP have worse outcomes than those whose resection is completed minimally invasive 22 .…”
Section: Discussionmentioning
confidence: 99%